Swiss wastewater treatment plant selects WABAG technology. Issue 10 (October 2015) - Unknown
Abstract : The Swiss winter resort of Lauterbrunnen is to upgrade its wastewater treatment plant with membrane technology from WABAG to deal with seasonal peak loads.